Cheng Hoon Teng temple virtual tourism application - Tan, Hong Qian (2024)
This project is a Virtual Tourism Application Using AR for Tourist Attraction. This project involves in the field of Computer Science and Augmented Reality (AR). After Covid-19 Pandemic, the tourism industry in Malaysia has been affected since public are preferred to stay at home rather than travelling outside to decrease the risk of Covid-19 infection. Although Malaysia is a small country, but the geographic limitation between each state still occurred. Besides, most of the people nowadays have fulfil their life with work and sometimes they want to travel outside alone in order to enjoy their personal space but they feel afraid because do not have any past experiences. Most of the problem mentioned above can be solved through our application. The methodology used in this project is ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) and discovery approach. Unity and Blender will be used as the software required for this project to build the 3D Model and combine those models to give users an impressive virtual travelling experience. Extensive research has been done in the literature review part in order to let developers know about the strength and weakness of each existing application. So that developers can based on this information to build a virtual tourism application which can help users to solve their recent facing problems from the existing application. As a result, the virtual tourism app successfully combines AR technology with tourism industry and it has demonstrated the feasibility of leveraging AR for transforming traditional tourism. Furthermore, the author also allows users to provide feedback to them for continuous improvement in the future. In conclusion, this project has shown the potential of cooperation between AR technology and traditional tourism which can bring different and unique travel experiences to users.